124: "But we're not Like the People on TV: A Qualitative Examination of the Influence of Media Messages on the Lives, Beliefs, and Health Behaviours of Pregnant and Parenting Adolescents". Issue 6 (1st June 2014) - Harrison, M; Worth, K; Rohde, K; Clarkin, C
Abstract: BACKGROUND: The media has long been established as a powerful socializing agent for youth. Recently, there has been an upsurge in media portraying teen pregnancy and parenting, such as 'Teen Mom'. While this type of programming is tailored to teens, research has not yet examined ways in which pregnant and parenting adolescents deconstruct these media messages. Moreover, it remains unknown whether media depictions of teenage motherhood shape the meanings pregnant teens and young parents construct about health and well being, and whether these perceptions influence their health behaviours. OBJECTIVES: This study explored pregnant and parenting teens' experiences with and perceptions of media messages portraying teen pregnancy, as well as how media messages influenced their social and health interactions. DESIGN/METHODS: Five focus groups were conducted at two urban community centres that service pregnant youth and young parents. A convenience sample of 26 participants was recruited across both sites. Focus groups were audio recorded and transcribed verbatim, then analyzed thematically. To establish trustworthiness in the findings, the researchers triangulated focus group data, maintained an audit trail and engaged in peer debriefing. RESULTS: Participants were a mean age of 18.7 years, and accessed broadcast media, print media and film containing teen pregnancy and parenting content. Participants were acutely aware of the negative impact of media messages on public perception, noting that the storylines in television reality programming were highly incongruent with their lived experiences. They felt these representations glamorized teenage pregnancy while failing to capture other realities of teenage parenting, such as the financial struggles and necessary role transitions. Moreover, that these representations reinforce damaging stereotypes, render maternal judgement and criticism socially acceptable, and create a double standard for teen parents. They felt that healthcare providers were not immune to media messaging; some participants reported withdrawing socially and delayed accessing health services because of the media-fuelled public views. CONCLUSIONS: This study highlights the need for heightened awareness of the influence of popular media on the construction of notions of teen pregnancy and parenting. Acknowledging and challenging stereotypes of teen pregnancy, as well as initiating dialogue with youth about the impact media has in their lives, could act as a protective factor to empower pregnant and parenting teens to engage with healthcare. To enhance the quality of care provided, healthcare providers should elicit the stories of pregnant youth and young parents, and consider their own biases when servicing this vulnerable group.